The endogeneity of optimum currency area criteria, intraindustry trade and EMU enlargement - Jarko Fidrmuc (Bank of Finland, Institute for Economies in Transition (BOFIT), 2001)
This paper tests an endogeneity hypothesis of optimum currency area (OCA) criteria (Frankel and Rose, 1998) on a cross-section of OECD countries between 1990 and 1999.The findings indicate that convergence of business cycles relates to intra-industry trade, but has no direct relation between business cycles and bilateral trade intensity.As far as intra-industry trade is positively correlated with trade intensities, this result confirms the OCA endogeneity hypothesis.The endogeneity of OCA linkage criteria implies extensive business cycle harmonization between CEECs and EU countries in the medium term.
URN:NBN:fi:bof-201408072015
Keywords: 330